Book Review – Breakdown: The Inside Story of the Rise and Fall of Heenan Blaikie by Norman Bacal - Del Gobbo, Daniel (2017)
The Canadian legal landscape is changing. Data over the last three decades show a trend toward larger law firms. Many of the country’s most storied ‘big law’ corporate firms have exploded in size and reach. Almost all of these firms maintain offices across the country and satellite offices in key international markets. Other large firms have been subsumed into foreign conglomerates pursuing expansion into the Canadian legal market. These developments have led to an increase in revenues and business opportunities for senior partners at these firms. It has also led to unprecedented challenges for the management of big law firms in Canada. As one of the former managing partners of Heenan Blaikie LLP (Heenan Blaikie), Norman Bacal knows this better than most.
Keywords: Daniel Del Gobbo